Bioremediation potential of seaweed (Gracilariopsis bailiniae) and tilapia (Tilapia mossambica) in intensive shrimp (Litopenaeus vannamei) culture - Elle, Bessie Joy G. (University of the Philippines Visayas, 2017)
Shrimp production has grown rapidly but it has been responsible for ecosystems failure because of its nutrient rich effluents. This study was conducted to investigate the potential of seaweed (Gracilariopsis bailiniae) and tilapia (Tilapia mossambica) to improve water quality and growth performance of Pacific white shrimp (LLitopenaeus vannamei) in an intensive recirculating low water exchange culture system, determine nutrient removal rates of G. bailiniae to biofilter nutrients from an intensive shrimp culture effluents and assess feasibility of shrimp-seaweed-tilapia culture. The results showed that seaweed (G. bailiniae) and tilapia (T. mossambica) have the potential to improve water quality in an intensive recirculating low water exchange culture system. Both G. bailiniae and T. mossambica have the potential to control the growth of pathogenic Vibrio and encouraged the stable growth of beneficial phytoplankton which control blooms and collapse of phytoplankton that affects growth and survival of shrimps. Mean removal efficiency of G. bailiniae of 20% reactive phosphorous, 41% unionized ammonia, 76% nitrite, and 53% nitrate confirmed the effectiveness of G. bailiniae to biofilter nutrients and improve water quality of an intensive shrimp effluents. Nuisance algae and suspended particles were found to affect biofiltering capacity and growth of G. bailiniae. Although, growth of tilapia (T. mossambica) and seaweed (G. bailiniae) were of moderate quantities, it gave additional production to the system. Both could be cultivated together without affecting the growth of Pacific white shrimps. These findings showed the feasibility of intensive low water exchange shrimp-seaweed, shrimp-tilapia, and shrimp-seaweed-tilapia tank culture.